2021
DOI: 10.3390/nano11112892
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Nanopolymers for Blood–Brain Barrier Delivery and Inhibition of Glioblastoma Growth through EGFR/EGFRvIII, c-Myc, and PD-1

Abstract: Glioblastoma (GBM) is the most prevalent primary brain cancer in the pediatric and adult population. It is known as an untreatable tumor in urgent need of new therapeutic approaches. The objective of this work was to develop multifunctional nanomedicines to treat GBM in clinical practice using combination therapy for several targets. We developed multifunctional nanopolymers (MNPs) based on a naturally derived biopolymer, poly(β-L-malic) acid, which are suitable for central nervous system (CNS) treatment. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The design of advanced nanomaterials , for various high-technology assets such as sensors, , light-emitting diodes, energy harvesting and converting devices, , electronics, transportation, , biomedical devices, electronic equipment for aerospace technology, , satellite technology, and other applications has been becoming a topic of growing interest. Particularly, this is driven by the growing need for environmental protection and monitoring of ecological situations under extremely severe conditions in highly polluted and poisoned areas.…”
Section: Introductionmentioning
confidence: 99%
“…The design of advanced nanomaterials , for various high-technology assets such as sensors, , light-emitting diodes, energy harvesting and converting devices, , electronics, transportation, , biomedical devices, electronic equipment for aerospace technology, , satellite technology, and other applications has been becoming a topic of growing interest. Particularly, this is driven by the growing need for environmental protection and monitoring of ecological situations under extremely severe conditions in highly polluted and poisoned areas.…”
Section: Introductionmentioning
confidence: 99%
“…This facilitates receptor-mediated transcytosis of LNP through the BBB and into the brain extracellular space 187 . Notably, multifunctional nanopolymers (MNPs) have been also used for the therapy of CNS owing to the capacity to cross the BBB 188 . Remarkably, Sun et al have studied the application of a CNS-selective delivery system, employing saposin C-dioleoylphosphatidylserine (DOPS) nanovesicles for neuronopathic GD therapy and revealed that the administration of a saposin C-DOPS-GCase successfully delivers functional GCase across a range of tissues, with a pronounced affinity for the brain 189 .…”
Section: Challengesmentioning
confidence: 99%
“…Therefore, the need for more effective and less toxic treatments remains a pressing concern in the scientific and clinical communities. Current and continuous research endeavors hold the promise of uncovering novel strategies to address the complexities of GBM treatment [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Researchers are actively engaged in exploring novel strategies that could provide more effective and advanced solutions for managing the complex and aggressive GBM tumor, including boron neutron capture therapy (BNCT).…”
Section: Introductionmentioning
confidence: 99%